PENGARUSUTAMAAN MODERASI BERAGAMA MELALUI MEDIA SOSIAL SEBAGAI UPAYA MENANGKAL RADIKALISME DI KALANGAN PELAJAR MILENNIAL SLTA KOTA KEDIRI - Zetty Azizatun Ni’mah (MAN 1 Kota Kediri, 2022)
Religious issues that bring intolerance, radicalism, and anti-local culture presented by social media to millennial students become negative tutorials that lead to a radicalism mindset in the life of religion and the nation. radicalism has become a fairly high case during the pandemic. The spread of radicalism is carried out through social media by broadcasting activities that have gone viral so that they become massive. The main purpose of religious moderation through the digital realm is none other than to voice moderate and tolerant religious narratives. It is hoped that the voice of religious moderation values ​​through social media can be disseminated massively either through IG, Face Book, WA, Twitter, Youtube, Tiktok, etc. so that it becomes a familiar narrative for students. A familiar term will become something viral and will be followed by a trend by millennial students as well as an air of assumptions for those who have been exposed to radicalism. The main topics of discussion in this research are: 1. What are the assumptions of high school millennial students in Kediri City regarding issues of intolerance on social media? 2. How are the efforts of stakeholders in mainstreaming religious moderation to millennial students of Kediri City Senior High School as an antidote to radicalism through social media? 38.6% of high school students in the city of Kediri agree on issues that lead to radicals. The assumptions they build are part of Islamic teachings that must be obeyed. This data was obtained from a number of 50 respondents from high school and Madrasah Aliyah students throughout the City of Kediri, 90% of whom were active social media users. The incessant voice of religious moderation by stakeholders (Ministry of Religion, Ministry of National Education, schools and madrasas) through social media is expected to have moderate religious values ​​such as the value of tawasut, the value of tawaznu, the value of i'tidal, the value of tasamuh, the value of musawah, the value of shura, the value of islah, awlawiyah values, tathawwur wal ibkar values, and tahadhur values ​​are massively internalized and socialized through social media be it IG, Face Book, WA, Twitter, Youtube, Tiktok etc. so that they become familiar narratives for students. Familiar terms will become something viral and millennial students will follow the trend